If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 7h = 8 + 9h Solving 10 + 7h = 8 + 9h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-9h' to each side of the equation. 10 + 7h + -9h = 8 + 9h + -9h Combine like terms: 7h + -9h = -2h 10 + -2h = 8 + 9h + -9h Combine like terms: 9h + -9h = 0 10 + -2h = 8 + 0 10 + -2h = 8 Add '-10' to each side of the equation. 10 + -10 + -2h = 8 + -10 Combine like terms: 10 + -10 = 0 0 + -2h = 8 + -10 -2h = 8 + -10 Combine like terms: 8 + -10 = -2 -2h = -2 Divide each side by '-2'. h = 1 Simplifying h = 1
| -5r=-10r+10 | | 6x+5=9x | | -5+5b=10b | | (-5x+3)(-7x+2)= | | 10-3k=4 | | -12z-5z=85 | | (4-1)m=3 | | 38-2x=7x+19 | | 3z+8z=8z-6+4z | | 6x+8-2x=-3 | | 2m+5=3(m-7)-2m | | 84-19x=-7(60+4) | | 95-5x=10+20 | | 4-9=27 | | x+3.3-8.4=6.2 | | 4x-9(x+1)=sqrt(7)-5x | | -5v=-6v+9 | | x^2+76x=0 | | -7r-3+2r=-(3-r) | | p+7=2p | | 8p+56=5p-4 | | 15.7=6.28r | | (x+4)-10=-15 | | 2p+2(3p-9)=6 | | 15.7=6.28 | | 4(x-3)+6=2(x+1) | | 2x-2=10x+1 | | 8+2x=5x-13 | | n+18=7 | | 10x-x-2x-x= | | 11x+25=7x+5 | | -3x-9=2x+7 |